What is the vulnerability of a food system to global environmental change? - Ericksen, Polly J. (2008)
Assessing the vulnerability of broadly described food systems to global environmental change requires a new, synthetic approach. Food systems can best be conceptualized as the integration of humans and the environment or coupled social-ecological systems. However, much of the existing literature on vulnerability assessment focuses on either social or ecological systems, and conceptual gaps limit the holistic evaluation of linked systems in which both social and ecosystem outcomes are important. I suggest an approach with which to integrate factors across a food system to assess the system's vulnerability to environmental change by focusing on key processes and system characteristics. However, the multiple objectives of different actors in food systems make tradeoffs inevitable and complicate the evaluation of vulnerability. Further development and use of this approach is a promising avenue for future research because empirical evidence is needed to further elaborate these understandings.